Fluid dynamics of air in a packed bed: velocity profiles and the continuum model assumption - NEGRINI, A. L.; FUELBER, A.; FREIRE, J. T.; THOMÉO, J. C. [UNESP] (Brazilian Society of Chemical Engineering, 1999)
Air flow through packed beds was analyzed experimentally under conditions ranging from those that reinforce the effect of the wall on the void fraction to those that minimize it. The packing was spherical particles, with a tube-to-particle diameter ratio (D/dp) between 3 and 60. Air flow rates were maintained between 1.3 and 4.44 m3/min, and gas velocity was measured with a Pitot tube positioned above the bed exit. Measurements were made at various radial and angular coordinate values, allowing the distribution of air flow across the bed to be described in detail. Comparison of the experimentally observed radial profiles with those derived from published equations revealed that at high D/dp ratios the measured and calculated velocity profiles behaved similarly. At low ratios, oscillations in the velocity profiles agreed with those in the voidage profiles, signifying that treating the porous medium as a continuum medium is questionable in these cases.
Keywords: Fluid Mechanics; Porous Media; Continuum Model; Fixed Bed; Velocity Measurements; Bed Structure